The Implications of the Diving Response in Reducing Panic Symptoms - Kyriakoulis, Peter; Kyrios, Michael; Nardi, Antonio Egidio; Freire, Rafael C.; Schier, Mark (Frontiers in Psychiatry, 2021)
Increased CO2 sensitivity is common in panic disorder (PD) patients. Free divers who are known for their exceptional breathing control have lower CO2 sensitivity due to training effects. This study aimed to investigate the immediate effects of cold facial immersion (CFI), breath holding and CO2 challenges on panic symptoms. Healthy participants and patients with PD were subjected to four experimental conditions in a randomly assigned order. The four conditions were (a) breath-holding (BH), (b) CFI for 30 s, (c) CO2 challenge, and (d) CO2 challenge followed by CFI. Participants completed a battery of psychological measures, and physiological data (heart rate and respiration rate) were collected following each experimental condition. Participants with PD were unable to hold their breath for as long as normal controls; however, this finding was not significant, potentially due to a small sample size. Significant reductions in both physiological and cognitive symptoms of panic were noted in the clinical group following the CFI task. As hypothesized, the CFI task exerted demonstrable anxiolytic effects in the clinical group in this study by reducing heart rate significantly and lessening self-reported symptoms of anxiety and panic. This outcome demonstrates the promise of the CFI task for clinical applications.